ENHANCING STUDENTS' READING COMPREHENSION THROUGH FABLES IN ELEMENTARY SCHOOL - Hariyono; Hasana, Firdausy Alya; Siadari, Yoshua Veron Handika Putra; Riza, Dwi Ainur; Salsabila, Anindya Thalita; Pasopati, Rommel Utungga (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2025)
This article describes the community service initiative that students and faculty members from Universitas Dr. Soetomo carried out for the SDN Kapasari I elementary school children to enhance their reading comprehension skills. The primary aim of this community service project is to enhance reading habits, including reading comprehension as well. This community service is executed through an initial evaluation, service provision, and assessment. This study employs documentation as its approach. Approximately fifty students from SDN Kapasari I participated in the event, which was successfully concluded. They are urged to read the designated fables both out loud and quietly. The main objective is to encourage students to cultivate reading habits to enhance their knowledge of literary pieces. In summary, this community project enables primary school students to enhance their comprehension of English literature and increases their self-assurance when speaking publicly. The implication is intended to widen students’ perspectives of knowledge regarding reading materials through its reading comprehension.